2020
DOI: 10.9778/cmajo.20190149
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of maternal adverse childhood experiences to understanding children’s externalizing and internalizing behaviours at age 5: findings from the All Our Families cohort

Abstract: Background:The negative effect of adverse childhood experiences (ACEs) on physical and mental health has led to calls for routine screening for ACEs in primary care settings. We aimed to examine the association between maternal ACEs and children's behaviour problems (externalizing and internalizing) at age 5 in the context of other known predictors.Methods: We analyzed data from mother-and-child dyads participating in the All Our Families cohort in Calgary, Canada, between 2011 and 2017. Data were collected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
(62 reference statements)
0
17
0
Order By: Relevance
“… 14 For anxiety, cutoff scores for the STAI-SF have not been consistently established but a cutoff of 1 SD above the mean for anxiety has been used in previous literature. 19 , 20 We therefore used a STAI-SF score 1 SD above the mean at the 8-year timepoint to define clinically significant anxiety at all timepoints (total anxiety score ≥14) because the mean calculated for the 8-year timepoint was most proximal to the COVID-19 impact survey timepoint and had the highest cutoff across data collection waves, providing the most conservative estimate.…”
Section: Methodsmentioning
confidence: 99%
“… 14 For anxiety, cutoff scores for the STAI-SF have not been consistently established but a cutoff of 1 SD above the mean for anxiety has been used in previous literature. 19 , 20 We therefore used a STAI-SF score 1 SD above the mean at the 8-year timepoint to define clinically significant anxiety at all timepoints (total anxiety score ≥14) because the mean calculated for the 8-year timepoint was most proximal to the COVID-19 impact survey timepoint and had the highest cutoff across data collection waves, providing the most conservative estimate.…”
Section: Methodsmentioning
confidence: 99%
“…At infant age 36 months, mothers were asked to recall ACEs that occurred in their lives before the age of 18 using a detailed questionnaire adapted from the original ACE checklist [45]. For consistency with the original scoring of Felitti et al and in response to pilot testing, questions were simplified for some of the original ACE questions to elicit yes/no responses instead of frequencies (often/very often) during data collection [46]. Detailed information about specific ACE questions used in this study can be found in Table 1.…”
Section: Acesmentioning
confidence: 99%
“…For consistency with the original scoring of Felitti et al and in response to pilot testing, questions were simpli ed for some of the original ACE questions to elicit yes/no responses instead of frequencies (often/very often) during data collection. 36 Detailed information about speci c ACE questions used in this study can be found in Hetherington et al (2020) Appendix 1. 36…”
Section: Acesmentioning
confidence: 99%
“…36 Detailed information about speci c ACE questions used in this study can be found in Hetherington et al (2020) Appendix 1. 36…”
Section: Acesmentioning
confidence: 99%